Dynamic memory management for embedded systems - Atienza Alonso, David (Springer International Publishing, 2015)
This book provides a systematic and unified methodology, including basic principles and reusable processes, for dynamic memory management (DMM) in embedded systems. The authors describe in detail how to design and optimize the use of dynamic memory in modern, multimedia and network applications, targeting the latest generation of portable embedded systems, such as smartphones. Coverage includes a variety of design and optimization topics in electronic design automation of DMM, from high-level software optimization to microarchitecture-level hardware support. The authors describe the design of multi-layer dynamic data structures for the final memory hierarchy layers of the target portable embedded systems and how to create a low-fragmentation, cost-efficient, dynamic memory management subsystem out of configurable components for the particular memory allocation and de-allocation patterns for each type of application. The design methodology described in this book is based on propagating constraints among design decisions from multiple abstraction levels (both hardware and software) and customizing DMM according to application-specific data access and storage behaviors. · Provides a systematic and reusable methodology for DMM to address concerns ranging from software design to hardware-based memory management and system optimization; · Describes in detail which optimization is the best candidate in DMM for each type of portable embedded system; · Includes extensive examples with code excerpts, demonstrating application to multiple application domains related to multimedia and networking; · Uses real industrial case studies to demonstrate the presented methodolo